PERAN MEDIASI BRAND IMAGE DALAM HUBUNGAN ANTARA LIFESTYLE, E-WOM, DAN BRAND TRUST TERHADAP MINAT PEMBELIAN SEPATU ADIDAS - Cahyono, Okky Dwi; Pakarti, Piji; Chasana, Amalia Nur; Fatmawati , Elia Resha (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: The research conducted aims to analyze the influence of lifestyle, E-WOM, and brand trust on the purchase intention of Adidas shoes with brand image as a mediating variable. Methods: This research was conducted with a quantitative approach, where a questionnaire was used as the main tool for data collection. The sampling technique applied was purposive sampling, by applying the Hair formula to determine the number of samples, which amounted to 150 respondents. The respondents were consumers who had purchased Adidas brand shoes. Data analysis was carried out using SmartPLS 4 software. Results: The results of the study revealed that lifestyle, E-WOM, and brand trust had a positive and significant effect on purchase intention, then lifestyle, E-WOM, and brand trust also had a significant positive effect on brand image. Meanwhile, brand image was not able to mediate the influence of lifestyle, E-WOM, and brand trust on the purchase intention of Adidas shoes. Keywords: Lifestyle, E-WOM, Brand Trust, Minat Beli, Brand Image.